Morphological comparison of genetically differentiated Polymorphus cf. minutus types - Grabner, Daniel; Doliwa, Annemie; Bulantová, Jana; Horák, Petr; Sures, Bernd (Parasitology research, 2020)
In the present study, we analyzed the morphology of three genetic types of the bird-infecting acanthocephalan Polymorphus cf. minutus (PspT1, PspT2, PspT3), mainly based on the cystacanth-stage obtained from amphipods (Gammarus fossarum, Gammarus pulex, Gammarus roeselii, Echinogammarus spp.). Males and females were pooled as there was no considerable difference between the sexes concerning the hook measurements. Additionally, we conducted a laboratory infection of one domestic duck for each Polymorphus type, to compare their performance and localization in this host species, and to obtain adult specimens for morphological comparison. The recovery rate from the ducks 4 weeks after infection was 16% for PspT1, 23.8% for PspT2, and 25% for PspT3. The adult worms were gravid, and the females contained mature eggs. Hook size did not differ considerably between cystacanths and adults of the respective type. The three Polymorphus types could be distinguished based on the cystacanth stage by a linear discriminant analysis that included hook measurements, proboscis length, proboscis width, and number of longitudinal hook rows and hooks per row. Furthermore, PspT3 was more different from PspT1 and PspT2 than the latter types from each other. Mainly the number of longitudinal hook rows differed in PspT3 from the existing descriptions of P. minutus (mainly 14 vs. mainly 16 rows). Potentially, PspT3 could be a non-indigenous parasite that was introduced with G. roeselii and that adapted to use the indigenous G. pulex as a host, while PspT2 might have been introduced to central Europe together with Echinogammarus spp.
Keywords: Male; Host-Parasite Interactions; interakce hostitele a parazita; Amphipoda; buněčná diferenciace; Europe; mužské pohlaví; helmintózy zvířat; Evropa; ptáci; Birds; Animals; ženské pohlaví; kachny; zvířata; Female; Acanthocephala; Helminthiasis, Animal; Ducks; Cell Differentiation